The evolutionary origins of chordate hematopoiesis and vertebrate endothelia - Pascual-Anaya, Juan; Albuixech-Crespo, Beatriz; Somorjai, Ildikó M. L.; Carmona-Mejías, Rita María; Oisi, Yasuhiro; Álvarez, Susana; Kuratani, Shigeru; Muñoz-Chápuli-Oriol, Ramón; Garcia-Fernàndez, Jordi (Elsevier, 2013)
The vertebrate circulatory system is the most complex vascular system among those of metazoans, with key innovations including a multi-chambered heart and highly specialized blood cells. Invertebrate vessels, on the other hand, consist of hemal spaces between the basal laminae of epithelia. How the evolutionary transition from an invertebrate-type system to the complex vertebrate one occurred is, however, poorly understood. We investigate here the development of the cardiovascular system of the cephalochordate amphioxus Branchiostoma lanceolatum in order to gain insight into the origin of the vertebrate cardiovascular system. The cardiac markers Hand, Csx (Nkx2-5) and Tbx4/5 reveal a broad cardiac-like domain in amphioxus; such a decentralized organization during development parallels that seen in the adult anatomy. Our data therefore support the hypothesis that amphioxus never possessed a proper heart, even transiently during development. We also define a putative hematopoietic domain, supported by the expression of the hematopoietic markers Scl and Pdvegfr. We show that this area is closed to the dorsal aorta anlages, partially linked to excretory tissues, and that its development is regulated by retinoic acid, thus recalling the aorta-gonads-mesonephros (AGM) area of vertebrates. This region probably produces Pdvegfr þ hemal cells, with an important role in amphioxus vessel formation, since treatments with an inhibitor of PDGFR/VEGFR lead to a decrease of Laminin in the basal laminae of developing vessels. Our results point to a chordate origin of hematopoiesis in an AGM-like area from where hemal Pdvegfrþ cells are produced. These Pdvegfrþ cells probably resemble the ancestral chordate blood cells from which the vertebrate endothelium later originated.
Keywords: Hematopoyesis; Hematopoyesis; Anfioxo; Evolución de la sangre; Cordados